Databases for CNV in control and disease populations - Feuk, Lars (Henry Stewart Talks, 2009)
Databases for CNV in control and disease populations, Introduction to databases for capturing structural genetic variation, An overview of the Database of Genomic Variants, Challenges in annotating structural variation in light of imprecise data, Rapid technology development, Terminology used in the field, Biases in existing data, Overview of existing databases for copy number variation
Archived at 2021/02/25